2019
DOI: 10.26873/svr-774-2019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin E and Selenium Supplementation on the Performance, Reproductive Indices and Metabolic Status of Ossimi Ewes

Abstract: The objective of this study was to investigate the effects of pre and post-lambing intramuscular (i.m.) injections of vitamin E (VE) and selenium (Se) on the performance, reproductive indices and metabolic status of Ossimi ewes. A total of 20 pregnant ewes were divided randomly into two equal groups of ten animals. The control group (CG) was administered 3 ml of normal saline. The treated group (TG) was administered a combination of 5 mg of sodium selenite and 450 mg of VE twice weekly for 2 weeks pre and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…Cholesterol concentration was somewhat higher in the experimental lambs, which can probably be attributed to Se supplementation. Such an effect was also noted by Abdel-Raheem et al [ 44 ] in ewes supplemented with Se. Lower serum cholesterol in control group lambs suggests that Se deficiency could impair liver function and cholesterol synthesis.…”
Section: Discussionsupporting
confidence: 81%
“…Cholesterol concentration was somewhat higher in the experimental lambs, which can probably be attributed to Se supplementation. Such an effect was also noted by Abdel-Raheem et al [ 44 ] in ewes supplemented with Se. Lower serum cholesterol in control group lambs suggests that Se deficiency could impair liver function and cholesterol synthesis.…”
Section: Discussionsupporting
confidence: 81%
“…The current finding showed that initially TAC level abruptly declined as parturition approaches, but supplementation of Vit E and Se inhibits a further decrease irrespective of the group in which TAC level declined around parturition, while in the case of nonpregnant goats, the supplementation inhibited the reduction of TAC level as the experiment advances. Our results are in accordance with previous studies where blood plasma TAC concentration was noticed higher in sheep and goats following the induction of Vit E and Se treatment [ 54 56 ]. Chauhan et al [ 34 ] also reported the elevated level of TAC in blood plasma after the same antioxidant injection.…”
Section: Discussionsupporting
confidence: 94%
“…The improved productivity of ewes and goats was consistent with the earlier experiments in terms of survival rate and daily weight gain of neonates [ 66 , 67 ]. Lambs raised by ewes treated with Vit E and Se in the last phase of gestation presented better weight gain than those not receiving any treatment [ 56 ]. A possible reason is due to the induction of Vit E and Se in the last trimester of pregnancy, increasing the transfer of Se to the growing fetus and enhancing its concentration in the colostrum as well as milk secretion, which improved feed intake efficiency and average daily weight gain [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the effect of higher doses of oleuropein supplementation resulted in similar TG concentrations when compared to the use of 100 mg/kg of vitamin E + 0.26 mg/kg of Se. Abdel-Raheem et al [31] also found TG decreased two weeks postpartum after 450 mg vitamin E and 5 mg Se supplementation twice weekly, similar to Saleh and Ebeid [36] in broilers supplemented with 0.5 mg/kg of Se.…”
Section: Discussionmentioning
confidence: 61%
“…This moderated effect in decreasing the blood glucose of this group (VEOLE) could be explained by its combination with the other antioxidants. Abdel-Raheem et al [31] found that supplementation of Se and vitamin E increased blood glucose in ewes. Metabolomic analyses of the liver tissue in rats with vitamin E deficiency had lower glucose content than those with a sufficient amount [32].…”
Section: Discussionmentioning
confidence: 99%